Development of a novel GTAW process for joining ultra-thin metal sheets - Manh, Ngo Huu; Nguyen, Van Anh; Duy, Han Le; Akihisa, Murata; Le, Van Thao; Ngoc, Trinh Quang; Gandham, Bharat (Elsevier, 2022)
The butt weld of ultra-thin sheet raw material coils in production lines is a crucial challenge with traditional welding processes because of the troubles related to the control of heat input, arc stability, application reliability, and investment costs. To overcome such challenges, a novel GTAW process has been developed for joining ultra-thin metal sheets for the first time. The novel welding torch with a novel orifice is the main discovered point of this process. In this paper, the novelties of the developed technology are clarified by comparing it with the conventional GTAW process. The results show that the novel GTAW process features much distinctiveness as compared to the conventional GTAW process: (i) the arc plasma column is more concentrated; (ii) the heat input is considerably reduced, but the temperature at the arc center is greatly increased; (iii) the metal evaporation and the metal vapor amount attached to the tungsten electrode surface are enormously reduced, and (iv) the corrosion of the tungsten electrode tip is vastly reduced. As a result, the novel GTAW process can successfully perform the butt weld of thin/ultra-thin metal sheets (up to 0.03 mm) with high quality and reliability.
Keywords: Novel GTAW process; Novel orifice; Ultra-thin metal sheet; Butt weld; Low heat input